Night eating syndrome, pola tidur, dan kebiasaan konsumsi sugar-sweetened beverage berdasarkan tipe metabolik pada mahasiswa obese - Anindita Putri Leksono; Fillah Fithra Dieny; Etika Ratna Noer; Ani Margawati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
Obesity prevalence in students is increasing and can lead to metabolic syndrome at a young age. The habit of harmful sleeping patterns, night eating syndrome, and excessive sugar-sweetened-beverage consumption can increase the risk of metabolic syndrome in obese students. This research aimed to analyze the differences between night eating syndrome, sleeping patterns, and consumption habits of sugar-sweetened beverages based on metabolic types in obese students. This research used a case-control design in Semarang in 2020, with 52 subjects aged 19-24 selected by consecutive sampling. The data included body weight using digital scales, height using microtoise, waist size using Medline, blood pressure using tensimeters, and laboratory tests to check triglyceride levels, HDL cholesterol, fasting blood glucose, and insulin. The instruments used were The Night Eating Questioner to assess the night eating syndrome, Pittsburg Sleep Quality to assess sleeping patterns, and the Semi-Quantitative Food Frequency Questionnaire to see the subject’s sugar-sweetened beverage consumption. The Chi-Square test analyzed the data. There was a difference between night eating syndrome (p=0,006) and sleeping pattern (p=0,012) in Metabolically Healthy Obesity (MHO) and Metabolically Unhealthy Obesity (MUO). There was no significant difference between sugar-sweetened beverage consumption in the two subject groups (p=0,714). In the MUO group, more people experienced poor sleep patterns and night-eating syndrome. Meanwhile, sugar-sweetened beverage consumption in the MHO and MUO groups was still considered normal.